In vitro delivery performance assessment of a new preloaded intraocular lens delivery system. Issue 12 (December 2016) - Wang, Lixin; Wolfe, Patricia; Chernosky, Alexis; Paliwal, Sumit; Tjia, Khiun; Lane, Stephen
Abstract : Purpose : To compare the delivery performance of a new preloaded intraocular lens (IOL) delivery system (Ultrasert [system U]) with that of 2 commercially available preloaded systems (iSert [system S] and Tecnis iTec [system T]), and a manual system (Monarch III D). Setting : Alcon Laboratories, Fort Worth, Texas, USA. Design : Experimental study. Methods : Freshly excised porcine eyes were randomly assigned to 5 groups of 10 eyes each as follows: preloaded systems U, S, T 2.2 mm incision, T 2.4 mm incision, and manual system. Corneal incision size was measured before and after delivery. The rate of successful in‐the‐bag IOL delivery, IOL adherence to the plunger tip, trapped trailing haptic, and presence of nozzle tip splitting were assessed. Statistical analysis was performed to determine the significance of differences between groups. Results : All systems successfully placed the IOL in the capsular bag. System U had the least corneal incision enlargement (mean 0.07 mm ± 0.05 [SD]) and the smallest final incision size (mean 2.31 ± 0.06 mm) ( P < .05). An associated split in the nozzle tip was observed for system S devices ( P < .05). Furthermore, in more than 50% of deliveries with system T, the IOL remained adhered to the plunger tip after exiting the nozzle ( P < .05). Systems S and T each had 1 occurrence of a trapped trailing haptic during IOL delivery. Conclusion : The new design of the system U with a depth‐guard nozzle tip allowed for the smallest incision enlargement with an absence of nozzle tip splitting and uneventful IOL delivery compared with the other preloaded systems tested in this study. Financial Disclosure : Drs. Tjia and Lane are consultants to Alcon Laboratories, Inc. Drs. Wang, Wolfe, Paliwal, and Miss Chernosky are employees of Alcon Laboratories, Inc.